2023
DOI: 10.3389/fpls.2023.1127006
|View full text |Cite
|
Sign up to set email alerts
|

Coregulation of glutamine synthetase1;2 (GLN1;2) and NADH-dependent glutamate synthase (GLT1) gene expression in Arabidopsis roots in response to ammonium supply

Abstract: Ammonium absorbed by roots is assimilated into amino acids. The glutamine synthetase/glutamate synthase (glutamine 2-oxoglutarate aminotransferase) (GS/GOGAT) cycle is essential to this biological process. In Arabidopsis thaliana, GLN1;2 and GLT1 are the GS and GOGAT isoenzymes induced in response to ammonium supply and playing key roles in ammonium utilization. Although recent studies suggest gene regulatory networks involved in transcriptional regulation of ammonium-responsive genes, direct regulatory mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…These findings suggest that the NH 4 + -responsive forms of GS/GOGAT have a central role in the primary assimilation of NH 4 + within the roots [188]. As the expression of these isoenzyme-encoding genes increases with NH 4 + availability, it is plausible to infer that plants possess a regulatory transcriptional network that modulates their gene expression in response to NH 4 + availability [185].…”
Section: Gs and Gogatmentioning
confidence: 96%
See 2 more Smart Citations
“…These findings suggest that the NH 4 + -responsive forms of GS/GOGAT have a central role in the primary assimilation of NH 4 + within the roots [188]. As the expression of these isoenzyme-encoding genes increases with NH 4 + availability, it is plausible to infer that plants possess a regulatory transcriptional network that modulates their gene expression in response to NH 4 + availability [185].…”
Section: Gs and Gogatmentioning
confidence: 96%
“…The coordinated action of GS and GOGAT is responsible for these interconnected processes [181][182][183]. Experimental studies involving reverse genetic analysis have demonstrated that the absence of genes encoding NH 4 +responsive GS/GOGAT isoenzymes reduces NH 4 + assimilation, particularly in the roots, resulting in impaired growth [184][185][186][187]. These findings suggest that the NH 4 + -responsive forms of GS/GOGAT have a central role in the primary assimilation of NH 4 + within the roots [188].…”
Section: Gs and Gogatmentioning
confidence: 99%
See 1 more Smart Citation